2015
DOI: 10.1111/mms.12266
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variability in the “vowel”‐like sounds of beluga whales (Delphinapterus leucas): Intra‐ and interpopulation comparisons

Abstract: The beluga whale (Delphinapterus leucas) has a rich and complicated vocal repertoire. However, different populations use similar and common types of signals. We studied physical features of one of these types, “vowels,” in three Russian populations: the White Sea population (European North), the Chukotka population (the Bering Sea, Chukotka), and the Okhotsk Sea population (Russian Far East) as well as in four summer aggregations of the White Sea belugas over several years in duration. The pulse repetition rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
(114 reference statements)
1
7
0
Order By: Relevance
“…Our findings on beluga SCC differences across populations that were most dissimilar across geographically summering areas are consistent with the observed geographic variation of median PRR in beluga whale “vowel” calls (Panova et al, 2016). This comparative study of three geographically separate Russian beluga populations reported that the “vowel” like sounds varied the most significantly between the two most remote populations, while the geographically closer populations had less pronounced variation (Panova et al, 2016). Our results closely mirror their findings, where geographically close populations displayed greater degrees of similarity in call structure, while the two most distant populations of EBS and the SLE were most dissimilar in LDA space.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings on beluga SCC differences across populations that were most dissimilar across geographically summering areas are consistent with the observed geographic variation of median PRR in beluga whale “vowel” calls (Panova et al, 2016). This comparative study of three geographically separate Russian beluga populations reported that the “vowel” like sounds varied the most significantly between the two most remote populations, while the geographically closer populations had less pronounced variation (Panova et al, 2016). Our results closely mirror their findings, where geographically close populations displayed greater degrees of similarity in call structure, while the two most distant populations of EBS and the SLE were most dissimilar in LDA space.…”
Section: Discussionsupporting
confidence: 91%
“…Although geographic variation in the vocal repertoire of beluga whales has not been widely examined, differences in acoustic communication signals among White Sea and Okhotsk Sea belugas in terms of time‐frequency parameters have been reported (Bel'kovich & Sh'ekotov, 1993). A comparative study by Panova et al (2016) examined three wild Russian beluga populations and found significant intraspecific variation in a short‐duration, pulsed beluga signal type they refer to as “vowel.” More recently, Panova et al (2019) detected microgeographic variability among some whistle signals produced by belugas inhabiting different locations of the White Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Using echolocation predictors for species classification is an effective approach, particularly given its primary sensory role for odontocetes. There is evidence for individual and group-specific call types among belugas 81 84 and narwhals 85 , which contributes to the variation in their vocal repertoire but also makes acoustic classification challenging. However, it is likely that echolocation clicks are characterized by more stable features due to their sensory function.…”
Section: Discussionmentioning
confidence: 99%
“…Using echolocation predictors for species classification is an effective approach, particularly given its primary sensory role for odontocetes. There is evidence for individual and group-specific call types among belugas [81][82][83][84] and narwhals 85 , which contributes to the variation in their vocal repertoire but also makes acoustic classification challenging. However, it is likely that echolocation clicks are characterized by more stable features due to their sensory function.…”
Section: Discussionmentioning
confidence: 99%